Vascularized versus Nonvascularized Facial Nerve Grafts Using a New Rabbit Model. Issue 2 (February 2015) - Zhu, Yun; Liu, Shengwen; Zhou, Shanghui; Yu, Zhiwei; Tian, Zhen; Zhang, Chenping; Yang, Wenjun
<x xml:space="preserve">Abstract</x> Background: The use of vascularized nerve graft models has been limited because of the complexity of the operation. The authors sought to develop a simple and effective rabbit model for facial nerve repair and evaluated its advantages over conventional nerve grafts. Methods: Rabbits were divided into three groups consisting of six rabbits each. The central auricular nerve and its nutrient vessels were used as a vascularized graft. Rabbits were grafted with a vascularized facial nerve graft (vascularized nerve graft group), with a free nerve graft (free nerve graft group), or with a vascularized nerve graft and a free nerve graft on each side of the face (vascularized nerve graft/free nerve graft group). Four months after surgery, facial performance and electrophysiologic monitoring were evaluated. The rabbits were then killed to prepare the nerve specimens for histologic, immunohistochemical, and transmission electron microscope study. Results: At 4 months after the facial nerve repair, the functional recovery of the facial nerve was observed and analyzed. The side grafted with vascularized nerve graft was superior to the side grafted with free nerve graft. Regenerated nerve fibers were observed in all groups, and rabbits grafted with vascularized nerve grafts had more regenerated axons than those that underwent free nerve grafting, although the regenerated nerves were not as good as the natural nerves. Conclusions: This study demonstrates that it is feasible to establish a vascularized nerve graft model in rabbits. The model offers the obvious advantages of operability and reliability. The vascularized nerve graft is demonstrated to have a superior value for facial nerve repair.